A study on the application of automatic license plate recognition system by using segmentation algorithm - Priyadharsan, K.; Selvi, N.Kalai; Arulselvi, T.R. (COMPUSOFT: An International Journal of Advanced Computer Technology, 2024)
Automatic license plate recognition is the extraction of vehicle license plate information from an image is sequence of image. The extracted information can be used with or without a database in many application system such as electronic payment system (tool payment, parking fee payment) and traffic surveillance. Automatic license plate reorganization uses either color black and white or infrared or camera to take images. In this work, novel hybrid algorithm is proposed for number plate recognition system through segmentation. License plate image are obtain from the camera. First step towards license plate image is to be scaled and preprocessed. Second approach the segmentation techniques are to be applied and extracted the license number from the license plate image. Finally the license numbers are compared with vehicle database and recognize the number plate.